2021
DOI: 10.3390/jof7100848
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiology of Invasive Fungal Disease in Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Invasive fungal disease (IFD) is a common cause of morbidity and mortality in patients with hematologic malignancies, especially among those undergoing allogeneic hematopoietic stem cell transplantation (HSCT). The epidemiology of IFD in HSCT patients has been evolving over the last decades, mainly in relation to changes in HSCT therapies such as antifungal prophylaxis. A progressive decrease in Candida albicans infection has been documented, alongside a progressive increase in infections caused by non-albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 83 publications
3
34
0
Order By: Relevance
“…Candida albicans has been identified as one of the most common nosocomial pathogens in recent years due to its ability to form biofilm and resistance to antimycotic agents (Bakhtiari et al, 2020; Mishra et al, 2014). They cause the most common invasive fungal infection and are the most frequent infection in hospitals worldwide (Brown et al, 2012; Osman et al, 2020; Puerta‐Alcalde & Garcia‐Vidal, 2021). Nearly, 65% of all human infections are due to microbial biofilm formation (Atriwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans has been identified as one of the most common nosocomial pathogens in recent years due to its ability to form biofilm and resistance to antimycotic agents (Bakhtiari et al, 2020; Mishra et al, 2014). They cause the most common invasive fungal infection and are the most frequent infection in hospitals worldwide (Brown et al, 2012; Osman et al, 2020; Puerta‐Alcalde & Garcia‐Vidal, 2021). Nearly, 65% of all human infections are due to microbial biofilm formation (Atriwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among susceptible patients with impaired immune functions for a variety of reasons, such as solid organ transplant recipients and hematopoietic stem cell transplant recipients, A. fumigatus , A. niger , A. terreus , and A. flavus are the most common isolated species of IA, but the role of cryptic species should not be overlooked [ 29 ]. Species that appear to be cryptic might be neglected because of misidentification and therefore, it would be difficult to assess their epidemiological distribution pattern and antifungal susceptibility profile [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This holds especially true in those patients who have received multiple prior lines of treatment [17,18]. IFD epidemiology in patients with haematological malignancies has been highly influenced by the widespread introduction of antifungal prophylaxis in high-risk populations [2]. At the beginning of the current century, fluconazole prophylaxis became the standard of care in neutropenic patients with haematological malignancies, since some trials had demonstrated a reduction in fungal infection and mortality [19][20][21].…”
Section: Non-aspergillus Mould Infections In Specific Populations And...mentioning
confidence: 99%